Sexual Health in Child and Adolescent Psychiatry: Multi-Site Implementation Through Synchronized Videoconferencing of an Educational Resource Using Standardized Patients - Drozdowicz, Linda; Gordon, Elisabeth; Shapiro, Desiree; Jacobson, Sansea; Zalpuri, Isheeta; Stewart, Colin; Lewis, A. Lee; Robinson, Lee; Myint, Myo Thwin; Daniolos, Peter; Williamson, Edwin D.; Pleak, Richard; et al. (Frontiers in Psychiatry, 2020)
Objective: Matters of sexuality and sexual health are common in the practice of child and adolescent psychiatry (CAP), yet clinicians can feel ill-equipped to address them with confidence. To address this gap in training and practice, we developed, implemented, and evaluated an educational module enhanced by videotaped depictions of expert clinicians interacting with professional actors performing as standardized patients (SPs). Methods: We developed an educational resource highlighting common issues of sexual health relevant to CAP practice, including sexual development, psychotropic-related side effects, and sexuality in children with autism. We wrote original scripts, based on which two clinicians interacted with three SPs. Digital recordings were edited to yield 5 clips with a cumulative running time of 20 minutes. The clips were interspersed during a 90-minute session comprising didactic and interactive components. Due to the COVID-19 pandemic, we used synchronous videoconferencing, which allowed content dissemination to several training programs across the country. Results: We recruited 125 learners from 16 CAP training programs through the American Academy of Child and Adolescent Psychiatry’s Alliance for Learning and Innovation (AALI). Routine inquiry into adolescent patients’ sexual function was uncommon, reported by only 28% of participants, with ‘awkward’ and ‘uncomfortable’ the most common terms mentioned in reference to the clinical task. The didactic intervention led to measurable improvements after two weeks in skills and knowledge (p = 0.004) and in attitudes (p < 0.001). The three items with the greatest improvement were: a) availability of developmentally tailored resources; b) comfort in addressing sexual development with underage patients; and c) with parents or guardians of neurotypical or developmentally disabled patients (p < 0.001 for each). Conclusions: A sexual health curriculum enriched by video-based examples can lead to measurable improvement in outcomes pertinent to the clinical practice of CAP. These educational materials are available for distribution, use and adaptation by local instructors. Our study also provides proof-of-principle for the use of multisite educational initiatives through synchronized videoconferencing.